Analisis Studi Kelayakan Usaha “Ginza.id” - Shella Gilby Sapulette; Kathleen Asyera Risakotta (Indonesian Journal of Engagement, Community Services, Empowerment and Development, 2023)
There are lots of opportunities that can be used as ideas for starting a business. And a business opportunity with promising prospects and never empty of enthusiasts is one of them, for example, a feasibility study for a clothing business. Ginza.id is a business engaged in the women's clothing sector which has a simple and comfortable concept. Ginza.id also has a goal to improve the economy among young people. Ginza.id markets its products through social media such as personal websites and social media accounts namely Instagram and Facebook. This activity contains business feasibility studies which are reviewed from several aspects, namely market and marketing aspects, production engineering aspects, legal aspects, management aspects and financial aspects. Methods used a qualitative methods and data collection are interviews and documentation. From the analysis results, it can be concluded from various aspects that Ginza.id has business feasibility and is able to develop into a profitable business in the future